Ensiklopedia keputusan pilihan raya umum : Parlimen dan Dewan Undangan Negeri 1959-2004 (Book Digital, 2008)
Encyclopedia of Malaysian state general election results for State Legislative Assembly and Parliament from 1959 to 2004